Building bridges : case studies in collaborative governance in Canada - Rocan, Claude (Invenire, 2018)
"The case studies contained in this book show real-life examples of complex problems being addressed through collaboration. The problems confronting modern society are complex and do not lend themselves to simple solutions or linear decision-making. They require the involvement of many stake-holders. This is often brought about by networks, which bring together a multitude of players in the search for solutions to public policy issues. This can be challenging, as differing viewpoints and personalities, and often conflicting interests need to be acknowledged and reconciled. Yet without the involvement of all interested parties, "solutions" that emerge will likely be partial, distorted, and short-lived. The cases span a broad spectrum, including issues of poverty reduction, criminal gang reduction, environmental reparation, economic development for First Nations, building age-friendly communities, and co-management of fisheries. To reflect Canada's diversity, the case studies are located in a number of different regions of Canada. What emerges is not a formula to follow, nor a definite set of "success factors." Instead, using common categories for analysis, the case studies provide rich insights in the practical application of collaborative governance from those with direct experience. The result is a book that will be of interest both to practitioners and to students of governance, and to anyone hoping for a future where divisions in society can be more effectively bridged."--